THE EFFECT OF FINANCIAL LITERACY ON BUSINESS INTEREST: A CASE STUDY ON FEBI UINSI SAMARINDA STUDENTS - Eliza, Nova; Puspitasari, Dhea Octavia; Rahmi, Nur (Asian Journal of Islamic Economic Studies, 2024)
The aim of the research is to determine the influence of entrepreneurship education, financial literacy, family environment, and love of money on the current entrepreneurial intentions of students at the Faculty of Economics, Sultan Aji Muhammad Idris National Islamic University. This research is quantitative or uses numbers as a measure. Data was collected using a questionnaire or questionnaire using random sampling techniques and distributed to 150 respondents or students. In this research, researchers used descriptive data analysis techniques. The results of this research show that financial literacy has a positive impact on investment decisions and decisions to be interested in business development for the majority of students. Financial behavior has a positive influence on investment decisions.